2023
DOI: 10.1182/bloodadvances.2023010348
|View full text |Cite
|
Sign up to set email alerts
|

Nonrestrictive diet does not increase infections during post-HSCT neutropenia: data from a multicenter randomized trial

Abstract: Infections are a major cause of morbidity and mortality during neutropenia after chemo-radio therapy and hematopoietic stem cell transplantation (HSCT). The use of low-microbial Protective-Diet (PD) in the peri-transplant period is a standard of care despite its efficacy has never been tested prospectively. We conducted a multicenter, randomized, non-inferiority trial enrolling all consecutive adult patients undergoing high-dose-induction chemotherapy or HSCT with the objective to compare Non-Restrictive-Diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Regarding nutritional support with LBD or non-restrictive diet (NRD), the literature points out that the former has shown no benefit on infection rates or survival, in contrast with the routine use of low-microbial foods in clinical practice ( 39 ). Moreover, results from a recent randomized study by Stella et al ( 33 ) demonstrated that the frequency of infections, deaths, nutritional outcomes, and acute GvHD was not different in patients receiving LBD versus NRD during the neutropenic phase after HSCT. These results suggest that the use of a restrictive diet is an unnecessary burden for patients’ QoL, even if, undoubtedly, data are more mature in the autologous HSCT setting in which LBD should no longer be recommended.…”
Section: Nutrition and Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding nutritional support with LBD or non-restrictive diet (NRD), the literature points out that the former has shown no benefit on infection rates or survival, in contrast with the routine use of low-microbial foods in clinical practice ( 39 ). Moreover, results from a recent randomized study by Stella et al ( 33 ) demonstrated that the frequency of infections, deaths, nutritional outcomes, and acute GvHD was not different in patients receiving LBD versus NRD during the neutropenic phase after HSCT. These results suggest that the use of a restrictive diet is an unnecessary burden for patients’ QoL, even if, undoubtedly, data are more mature in the autologous HSCT setting in which LBD should no longer be recommended.…”
Section: Nutrition and Infectionsmentioning
confidence: 99%
“…Despite advances in supportive care, infections remain a significant cause of morbidity and mortality in the setting of HSCT ( 33 , 34 ). The resultant injury on the gastrointestinal epithelial barrier by chemotherapy (CT) or radiotherapy (RT), and the extensive use of antibiotics during the neutropenic phase, may lead to gut microbiota dysbiosis ( 35 ).…”
Section: Nutrition and Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Blood Advances , Stella et al report their findings from a multicenter trial that randomly assigned patients undergoing hematopoietic stem cell transplantation (HCT) to a traditional restrictive neutropenic diet or a liberalized diet. 1 More than 200 patients who underwent auto- and allo-HCT and underwent treatment at 3 transplant centers in Italy were included in the study, and the authors found that restricting posttransplant dietary options conferred no benefit with regard to the incidence of severe infections or any of the secondary outcomes studied. The key differences between the restrictive and liberalized diet recommendations are summarized in the figure.…”
mentioning
confidence: 99%